A comprehensive immunohistochemical and molecular approach to the PI3K/AKT/mTOR (phosphoinositide 3‐kinase/v‐akt murine thymoma viral oncogene/mammalian target of rapamycin) pathway in bladder urothelial carcinoma - Korkolopoulou, Penelope; Levidou, Georgia; Trigka, Eleni‐Andriana; Prekete, Niki; Karlou, Maria; Thymara, Irene; Sakellariou, Stratigoula; Fragkou, Paraskevi; Isaiadis, Dimitrios; Pavlopoulos, Petros; Patsouris, Efstratios; Saetta, Angelica A. (BJU international, 2012)
What's known on the subject? and What does the study add? A few published studies investigating single or various PI3K/AKT/mTOR signalling components have produced inconsistent results. Moreover, PI3K regulatory subunit p85a and activated p70S6K expression levels have not been previously examined in urothelial carcinoma (UC). The present study addresses simultaneously all key members of PI3K/AKT/mTOR signalling cascade supporting a differential implication of PI3K/AKT/mTOR pathway components in urothelial tumorigenesis. Furthermore, we propose p‐4E‐BP1 as a potential prognostic marker in UC, which might assist the selection of patients more likely to benefit from chemotherapy regimens based on PI3K/AKT/mTOR pathway inhibition. Finally, the present study indicates PIK3CA/AKT1 mutational status as a potential predictive marker for time‐to‐recurrence. OBJECTIVE • To perform a comprehensive simultaneous assessment of all key members of phosphoinositide 3‐kinase/v‐akt murine thymoma viral oncogene/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway along with AKT homolog 1 (AKT1) and PIK3 catalytic alpha polypeptide (PIK3CA) mutations in bladder urothelial carcinoma (UC). • Published information is limited to a few studies looking into single or various combinations of members of this pathway with inconsistent results. In particular the expression status of phosphorylated (p‐)p70S6 kinase (p70S6K) and p85a subunit of PI3K has not been tested in UC. PATIENTS AND METHODS • Paraffin‐embedded transurethral resection tissue from 113 patients with UC was investigated for the association of p85aPI3K, p‐AKT, p‐mTOR, p‐p70S6K and p‐4E‐BP1 (eukaryotic initiation factor 4E‐binding protein 1) expression status, as well as PIK3CA and AKT1 mutations with p‐extracellular signal‐regulated kinase 1/2 (ERK1/2), fibroblast growth factor receptor 3 (FGFR3), pathological features, recurrence and cancer‐specific survival. RESULTS • With the exception of p‐p70S6K, all others components of the PI3K/AKT/mTOR pathway were upregulated in UCs as compared with normal urothelium. • p‐mTOR expression strongly correlated with its upstream p‐AKT and marginally with its downstream p‐p70S6K. p85aPI3K and p‐ERK1/2 levels were also marginally correlated. • PIK3CA and AKT1 mutations were distinctly uncommon and mutually exclusive, without any association with pathological features. However, the presence of AKT1 mutations was associated with increased FGFR3 levels and was restricted to p85aPI3K immunonegative cases, whereas PIK3CA mutant cases had marginally lower p85aPI3K levels. • The presence of PIK3CA single or combined with AKT1 mutations was associated with shorter recurrence‐free survival in univariate survival analysis. An inverse relationship was established between p‐4E‐BP1 immunopositivity and histological grade or T category, as well as between p‐p70S6K levels and T category, the latter relationship being of marginal significance. • p‐4E‐BP1 nuclear expression was marginally associated with the presence of lymphovascular invasion and adversely affected survival in multivariate, but not in univariate analysis. CONCLUSIONS • PI3K/AKT/mTOR signalling components appear to be differentially implicated in urothelial tumorigenesis and, with the exception of p85aPI3K, are unrelated to the PIK3CA or AKT1 mutational status. • Our findings propose p‐4E‐BP1 as a potential prognostic marker in UC independent of its association with pathological features, which might assist the selection of patients more likely to benefit from PI3K/AKT/mTOR axis inhibition. • PIK3CA/AKT1 mutational status may have a place in the prediction of time‐to‐recurrence.